Simulation of UHMWPE Composites Filled with Preliminary Mechanically Activated PTFE Particles - Bochkareva S. A.; Grishaeva N. Yu.; Lyukshin P. A.; Lyukshin B. A.; Panin S. V. Sergey Viktorovich (2018, 2018)
Title screen